Evaluation of nickel and copper catalysts in biogas reforming for hydrogen production in SOFC - Silva,Leonardo Alves (2017)
ABSTRACT The solid oxide fuel cells (SOFC) enable the efficient generation of clean energy, fitting the current requirements of the growing demand for electricity and for the environment preservation. When powered with biogas (from digesters of municipal wastes), the SOFCs also contribute to reduce the environmental impact of these wastes. The most suitable route to produce hydrogen inside SOFC from biogas is through dry reforming but the catalyst is easily deactivated by coke, because of the high amounts of carbon in the stream. A promising way to overcome this drawback is by adding a second metal to nickel-based catalysts. Aiming to obtain active, selective and stable catalysts for biogas dry reforming, solids based on nickel (15%) and copper (5%) supported on aluminum and magnesium oxide were studied in this work. Samples were prepared by impregnating the support with nickel and copper nitrate, followed by calcination at 500, 600 and 800 oC. It was noted that all solids were made of nickel oxide, nickel aluminate and magnesium aluminate but no copper compound was found. The specific surface areas did not changed with calcination temperature but the nickel oxide average particles size increased. The solids reducibility decreased with increasing temperature. All catalysts were active in methane dry reforming, leading to similar conversions but different selectivities to hydrogen and different activities in water gas shift reaction (WGSR). This behavior was assigned to different interactions between nickel and copper, at different calcination temperatures. All catalysts were active in WGSR, decreasing the hydrogen to carbon monoxide molar ratio and producing water. The catalyst calcined at 500 oC was the most promising one, leading to the highest hydrogen yield, besides the advantage of being produced at the lowest calcination temperature, requiring less energy in its preparation.